Wage Formation in a Cointegrated VAR Model: A Demand and Supply Approach. - Thórarinn G. Pétursson; Torsten Sløk (University of Copenhagen, Economic Policy Research Unit (EPRU), 1997)
Usually cointegrated VAR models of wage formation are analysed in a wage-price setup. However, theoretical wage bargaining models provide the background for a wage-employment setup. The two relations of interest are the labour demand equation from the profit maximizing firms and the (bargained) wage equation from maximizing the Nash product of the wage bargaining process. From the underlying economic model we derive explicit parameter restrictions which are analysed using a multivariate cointegration approach, using quarterly data from Denmark. These restrictions are not rejected and the theoretical model with maximizing agents can be said to give a good description of wage formation in Denmark.
Keywords: 330